sa_pDNA_107ind_3190char - Gussarova, Galina; Allen, Geraldine A.; Mikhaylova, Yulia; McCormick, Laurie J.; Mirré, Virginia; Marr, Kendrick L.; Hebda, Richard J.; Brochmann, Christian (Dryad Digital Repository, 2015)
pDNA sequence file in nexus format. See description in ReadMe file.